Association between type 2 diabetes (T2D) and tooth loss: a systematic review and meta-analysis - Amir Reza Ahmadinia; Donya Rahebi; Masoud Mohammadi; Mousa Ghelichi-Ghojogh; Alireza Jafari; Firooz Esmaielzadeh; Abdolhalim Rajabi (BMC Endocrine Disorders, 2022)
Abstract Background Several studies have assessed the relationship between type 2 diabetes (T2D) and tooth loss; however, results have been inconsistent. Therefore, the present systematic review and meta-analysis of observational studies was designed to examine the association between T2D and tooth loss. Methods This systematic review and meta-analysis was conducted based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guideline. We searched all the relevant studies in international databases of Scopus, PubMed, ProQuest, Web of Science, Cochrane Library, and Google scholar search engine until February 2022. The heterogeneity of the studies was calculated using the I2 index. Measure of effect and 95% confidence interval (CI) were extracted from each study. The results of the study were analyzed using the random effects model. Results In the present study, 22 eligible studies were included. Meta-analysis of unadjusted and adjusted results showed that T2D significantly increased the risk of tooth loss, and Odds Ratio (OR) unadjusted was 1.87 (95% CI: 1.62–2.13, p < 0.001), and OR adjusted was 1.20 (95% CI: 1.10–1.30, p < 0.001), respectively. Subgroup analysis based on study design for adjusted OR indicated that in the cohort study (OR: 1.29, 95% CI: 1.07–1.51), in the cross-sectional study (OR: 1.15, 95% CI: 1.06–1.23), and in the case-control study (OR: 5.10, 95% CI: 1.01–9.18) there was a significant association between T2D and tooth loss. Other subgroups analyses showed consistent results and no publication bias existed. Conclusions The findings suggest that T2D is associated with increased risk of tooth loss. This conclusion may provide useful evidence for correlated clinical researches.